Water Use of Young Citrus as a Function of Irrigation Management and Ground Cover Condition - Aribi, Kamarudzaman (1986)
This paper describes the effect of irrigation and ground cover management on crop evapotranspiration (ET) of young Valencia citrus trees grown on Arredondo fine sand. Six different treatment combinations were used: three levels of sod water potential and two levels of ground cover conddion. Results obtained with grass cover treatments required 50% more water than with no grass cover treatments. Evapotranspiration correlated positively with the amount of irrigation applied. Month(y crop water use coefficients with grass cover treatments were 50% higher than with no grass cover treatments. Crop water use coefficient decreased as soil water potential decreased.